Estrategias de marketing para mejorar el posicionamiento en el mercado de la tienda “Humero” del cantón La Maná, provincia de Cotopaxi,2022 - Ayala Vega, Miriam Janeth (2023)
The current research has, as main objective to design marketing strategies to improve the positioning of the "Humero store", in La Maná canton, facing the problem of the low level about the store positioning. The methodology used was mixed, for the processing and analysis descriptive and inferential statistics were used but specifically descriptive research, taking as reference the macro areas that generally emphasize the variables. Not only bibliographic and field research were applied, but also inductive, deductive, and analytical methods. The techniques applied for the data collection about the owner and clients were the interview and the survey, and for the internal and external diagnosis the FODA matrix, while the positioning was determined by employing a graphic map. The results obtained showed weaknesses such as scarce information on products and prices, deficient management of promotions, and limited options in types of sales. The positioning level of the Humero store based on the quality and price attributes presents a regular positioning since it has not consolidated a differential factor compared to other competing establishments. In reference to the proposal the following strategies were proposed: products prices exhibition, product promotions, promotional combos, design a logo, setting up the mission, vision, and values, home sales, advertising on social networks, radio advertising, use of uniforms and badges and the implementation of a suggestion and complaints box, reflecting an estimated budget of $507.00.